2020
DOI: 10.1097/mpg.0000000000002687
|View full text |Cite
|
Sign up to set email alerts
|

Rules Are Meant to Be Broken

Abstract: Background and Aims: The “rule of 3” is a 40-year-old expert opinion that suggests dilating an esophageal stricture more than 3 mm is unsafe. Few studies have evaluated this tenet, and do not specify how much larger than 3 mm is reasonable. Our aim was to determine the optimal point for maximum dilation diameter with acceptable risk in a pediatric population. Methods: A retrospective review in pediatric patients with esophageal strictures was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…Esophageal dilation should not be increased by more than 3 mm in a single endoscopy to reduce the risk of perforation, the so-called "rule of 3"[ 18 , 19 ]. Clark, SJ founded that balloon dilations that expanded the initial esophageal osis ≤ 5 mm in a pediatric population appear to not unduly increase the risk of perforation in his research[ 20 ]. Non-adherence to the "rule of 3" does not appear to increase the risk of adverse events, particularly perforation, after esophageal dilation using bougie dilators[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal dilation should not be increased by more than 3 mm in a single endoscopy to reduce the risk of perforation, the so-called "rule of 3"[ 18 , 19 ]. Clark, SJ founded that balloon dilations that expanded the initial esophageal osis ≤ 5 mm in a pediatric population appear to not unduly increase the risk of perforation in his research[ 20 ]. Non-adherence to the "rule of 3" does not appear to increase the risk of adverse events, particularly perforation, after esophageal dilation using bougie dilators[ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The method of measuring esophageal stricture diameter was previously described (8,18). During endoscopy, we used live fluoroscopy with contrast to determine the greatest anastomotic diameter.…”
Section: Methodsmentioning
confidence: 99%
“…After stricture dilation as previously reported (18), the stent was placed either comparable to final balloon size or 1-2 mm greater. The diameter of the upper and lower esophagus were also noted on fluoroscopy, at the time of the endoscopy, to ensure that the diameter of the flared ends of the stents were not too large for the esophagus.…”
Section: Stent Placement/monitoringmentioning
confidence: 99%
“…Various etiologies can cause esophageal strictures and stenosis in children, with caustic, anastomotic, congenital, GERD, and eosinophilic esophagitis being the most common (22,(49)(50)(51)(52)(53)(54). To date, there are various endoscopic treatment options, of which endoluminal balloon dilatation is probably the most useful and safe.…”
Section: Advances In Endo-dilatation For Treatment Of Esophageal Sten...mentioning
confidence: 99%
“…The "rule of 3, " to prevent perforation, has been adopted from the ASGE recommendations and implies that the dilation of a stricture should not be greater than three times the diameter of the stricture. However, Clark et al have recently challenged this recommendation for children with stenosis of esophageal anastomosis: by reviewing charts from 284 children who underwent in total 1,384 balloon dilatations, they observed that dilatation of ≤5 mm did not unduly increase the risk of perforation, with a cumulative rate of perforation for dilatations ≤5 mm of 0.74%, whereas the risk increased to 4.85% in dilations ≥6 mm (49).…”
Section: Esophageal Dilatationmentioning
confidence: 99%